'Maya Altar' as a Theological and Inter-religious Experience - López Bac, Ernestina ca. 21. Jh. (Concilium, 2019)
The Maya Altar arose out of a community experience and the experience of God as family. Sharing in the Maya Altar, which is also known as the four ways, means working forfairness, justice and communion in harmony with human beings and creation. As an inter-religious experience, the Maya Altar accommodates both indigenous and Christian spirituality. The altar plays an important part in Teología India (Indigenous Theology) conferences, through which indigenous communities strengthen their spiritual, theological and practical experience.